The Effectiveness Study On User Interface Design (UID) For Local Cosmetic Website By Apllying Theories Of Aesthetics - Mihat, Mohammad Fariq (UTeM, 2016)
The aim of this research paper is to figure out user’s feelings about Graphical User Interface design on websites by adopting aesthetic theories. Five aesthetic principles are illustrated in the literature study, which are golden section, dynamic symmetry, Gestalt laws, colour harmony and Goethe’s colour theory. Qualitative research method is conducted as the way to explore user’s behaviour and feelings. The researcher provides two websites, one of which is designed by breaking down all those five theories and another one is designed by following all the aesthetic principles. Interviews are used as the method for collecting data from interviewees. The interviewees are selected from different department in Kolej Poly-Tech Mara Batu Pahat. Close-ended questionnaire and method is utilized by converting the interview conversation records to text-based data. Highlighting and marking the important and related data, and analysising do them the coding analysis by relating data to corresponding design theories. The study found that the website design by applying aesthetic theories provided better visual effect and usability to user. It not only visually pleased the user, but also helped users accomplish specific task efficiently and accurately. It is also give satisfaction to user when they look the website.